STRATEGI KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU DALAM MEMPROMOSIKAN OBJEK WISATA MONUMEN KERETA API DAN MAKAM PAHLAWAN KERJA - Ramadhan, Irfan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Located on Kaharuddin Nasution Street, Simpang Tiga, Bukit Raya, in Pekanbaru City, Riau, there is a tourist destination called the Railway Monument and the Heroes’ Cemetery. An effective communication strategy is essential to attract tourists and promote this site. The purpose of this study is to identify the communication strategy used in promoting the Railway Monument and the Heroes’ Cemetery. This research employs Lasswell’s communication model combined with a qualitative research methodology. Purposive sampling techniques were used, with subjects including the Pekanbaru City Department of Culture and Tourism, the General Affairs Subsection, the Content Creator Section, the Creative Economy Cooperation Section, and the Head of the Tourism Attraction Development Section. Data collection methods included interviews and observations. Data analysis techniques involved data reduction, data explanation, and drawing conclusions. The data validity was verified using triangulation techniques. The research findings indicate that the communication strategy of the Pekanbaru City Department of Culture and Tourism, which involves promoting educational historical content on social media platforms like Facebook, Instagram, YouTube, and others, has been quite effective, as evidenced by the increase in visitors to the Railway Monument and the Heroes’ Cemetery from January to May 2024. with a total of 763 visitors to the site out of 859,016 visitors to all tourist attractions in Pekanbaru. This represents a 95.9% increase from the total number of visitors to the Railway Monument and the Heroes' Cemetery in 2023, which was 796 out of 1,457,874 visitors to all tourist attractions in Pekanbaru. Keywords: Communication Strategy, Tourist Attraction, Promotion.